Differential Pulse Voltammetry Study for Quantitative Determination of Dysprosium (III) in Acetonitrile Solution - Wyantuti, Santhy; Pratomo, Uji; Shauvina, Shauvina A; Hartati, Yeni Wahyuni; Bahti, Husein Hernandi (International Journal of Renewable Energy Development, 2021)
Dysprosium has gained global interest due to its key application in renewable technology, such as wind power technology. The presence of this rare earth element (REE) can be determined by several spectroscopic methods. Recently, a voltammetry method has provided an alternative method for the simple and fast detection of REEs. However, to the best of our knowledge, this experiment is usually carried out in an aqueous solvent, and the response of the REE in an organic solvent by the voltammetry method has rarely been investigated. In this research, the quantitative detection of dysprosium and dysprosium mixtures with samarium, europium and gadolinium in acetonitrile is reported by differential pulse voltammetry. A Box-Behnken design was applied to predict the optimum condition of the measurements. Three factors, namely potential deposition, deposition time and amplitude modulation, were found to significantly influence the signal under optimal conditions, which are -1.0 V, 83.64 s and 0.0929 V, respectively. The surface characterization of dysprosium deposited on a Pt surface shows better deposition under 100% acetonitrile compared to a lower concentration of acetonitrile. The evaluation in this study shows a detection limit of 0.6462 mg•L-1 and a quantitation limit of 2.1419 mg•L-1, with a precision value and recovery value of 99.97% and 93.62%, respectively.